2016
DOI: 10.1136/bmjopen-2016-012078
|View full text |Cite
|
Sign up to set email alerts
|

Initial experience using a femtosecond laser cataract surgery system at a UK National Health Service cataract surgery day care centre

Abstract: ObjectivesTo describe the initial outcomes following installation of a cataract surgery laser system.SettingNational Health Service cataract surgery day care unit in North London, UK.Participants158 eyes of 150 patients undergoing laser-assisted cataract surgery.InterventionsLaser cataract surgery using the AMO Catalys femtosecond laser platform.Primary and secondary outcome measuresPrimary outcome measure: intraoperative complications including anterior and posterior capsule tears. Secondary outcome measures:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…More recently, the use of FLACS by residents has been shown to be well tolerated, albeit possibly less efficient than conventional techniques at the same stage of training. 32 34 Our study found a PCC rate of ~0.3% in both manual and laser cohorts, which is comparable to the best found in the current literature. Of importance is that the FLACS cohort represented all patients with minimal exclusions highlighting the potential use as a revised current benchmark target.…”
Section: Discussionsupporting
confidence: 88%
“…More recently, the use of FLACS by residents has been shown to be well tolerated, albeit possibly less efficient than conventional techniques at the same stage of training. 32 34 Our study found a PCC rate of ~0.3% in both manual and laser cohorts, which is comparable to the best found in the current literature. Of importance is that the FLACS cohort represented all patients with minimal exclusions highlighting the potential use as a revised current benchmark target.…”
Section: Discussionsupporting
confidence: 88%
“…There is a possible surgical learning curve effect for FLACS, with all trial surgeons having performed hundreds to thousands of conventional phacoemulsification cataract surgeries compared with a minimum of 10 FLACS cases to meet trial surgeon eligibility. We have previously published data on the learning curve for FLACS and found that complications tended to occur within the first few cases; 31 however, correspondence suggests the learning curve may include the first 100 cases for FLACS. 32 Even if the FLACS learning curve is 100 cases, the complication rate in the FLACS arm is low, and so it is difficult to see how this would materially affect our findings.…”
Section: Discussionmentioning
confidence: 97%
“…Importantly, we did not find too many instances of the capsular tears and pupillary miosis that had been reported previously. [ 14 15 19 20 21 There is a lot of debate regarding the integrity of the capsulotomy created by the femtosecond laser, predominantly initiated by electron microscopic studies showing ragged edges at the edge of the capsulorhexis. [ 22 ] However, this did not translate into complications as we saw visible capsular tags in only six eyes and radial tear occurred in only one eye.…”
Section: Discussionmentioning
confidence: 99%